1979
DOI: 10.1021/i260069a006
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Heterogeneously Catalyzed Free-Radical Oxidation of Phenol in Aqueous Solution

Abstract: A point to be noted is that the present model used the conduction heat transfer obtained independently based on the theory of conduction through contact spots, whereas the contribution of the convective heat transfer mode was determined separately under a unique experimental condition which decouples the convection mode from the conduction mode.Therefore, this model offers an independent estimate of the total heat transfer (Nut) which shows agreement with the experimental data reported in the literature. Nomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The critical nanocatalyst concentration phenomenon as observed in this work, is one of the characteristics of free radical chain reaction, in which a slight change in nanocatalyst loading (active phase loading and nanocatalyst loading in reactor) induces a noticeable change in the rate of process (Sadana, 1979). According to this mechanism, the nanocatalyst simultaneously plays dual roles of initiator and terminator of free radicals.…”
Section: Reaction Network Of Phenol Oxidation Over Synthesized Nanocamentioning
confidence: 63%
“…The critical nanocatalyst concentration phenomenon as observed in this work, is one of the characteristics of free radical chain reaction, in which a slight change in nanocatalyst loading (active phase loading and nanocatalyst loading in reactor) induces a noticeable change in the rate of process (Sadana, 1979). According to this mechanism, the nanocatalyst simultaneously plays dual roles of initiator and terminator of free radicals.…”
Section: Reaction Network Of Phenol Oxidation Over Synthesized Nanocamentioning
confidence: 63%
“…Recently, it was shown that the CCC value obtained (Sadana, 1979) from the available length of the induction period, rh data (Sadana and Katzer, 1974a) compared very favorably with the CCC value obtained from the expression developed for the kinetic chain length [when it equals 0.5 (Neuberg and Graydon, 1972)] in the steady-state activity regime. It is the purpose of this note to examine the effects of (a) temperature and reuse of supported CuO catalyst and (b) fresh supported Mn02 catalyst on CCC in aqueous-phase phenol oxidation utilizing induction period data for fresh and reused catalyst by the method linking with CCC (Sadana, 1979).…”
Section: Communicationsmentioning
confidence: 83%
“…Thus, the solid catalysts enhance the heterolytic reactions by the formation of ionic environment. Both free radical (homolytic) and ionic (heterolytic) oxidation reaction mechanisms have been proposed for the CWAO of organic compounds [190][191][192][193][194]. Sadana and Katzer [190] proposed a heterogeneous-homogeneous free radical mechanism consisting of the initiation on catalyst surface, homogeneous propagation, and either homogeneous or heterogeneous termination.…”
Section: Reaction Mechanisms and Pathwaysmentioning
confidence: 99%
“…Pintar and Levec [191,192] demonstrated that the CWAO of phenolic compounds combined a redox and a heterogeneous nonbranched chain free radical mechanism in which the role of catalyst was ascribed to be in the activation of phenol molecule and oxygen. The critical catalyst concentration phenomenon is one of the characteristics of free radical chain reaction, in which a slight increase in catalyst concentration induces a dramatic change in the rate of process [193]. Another is an induction period where the generation of radicals is poor, followed by a higher steady-state period with a fast free radical reaction regime [194].…”
Section: Reaction Mechanisms and Pathwaysmentioning
confidence: 99%